KONSERVATISME AKUNTANSI DIANTARA BOOK TAX DIFFERENCES, PENGUNGKAPAN CORPORATE GOVERNANCE DAN KUALITAS LABA - Tan Kwang En (Jurnal Akuntansi Manajerial (Managerial Accounting Journal), 2017)
Earnings information is one of many information that is needed, both by company’s internal and external parties. Therefore, the correct and reliable earnings information is something that should be done carefully by management. This study aims to analyze the influence of book tax differences and disclosure of corporate governance on the quality of earnings information published by the company. And since accounting conservatism indicates that investors do not appreciate the combination of changes in investment, accounting conservatism is used as a moderating variable. The samples used are companies listed on the Indonesia Stock Exchange and have a governance index from IICD (Indonesia Institute of Corporate Governance), so we collect samples of 30 firm-years. The results of this study conclude that book-tax differences and corporate governance disclosure have a positive and significant influence on earnings quality, while accounting conservatism weakens that relationship.